General method for carbon–heteroatom cross-coupling reactions via semiheterogeneous red-light metallaphotocatalysis - Geyang Song; Wei Zhang; Jiameng Song; Qi Li; Yuyu Feng; Hongyu Liang; Tengfei Kang; Jianyang Dong; Gang Li; Juan Fan; Xue-Peng Zhang; Quan Gu; et al. (Nature Communications)
Abstract Combining transition-metal catalysis with photocatalysis has emerged as a valuable, complementary approach for achieving carbon–heteroatom cross-coupling reactions. However, the need to use blue or high-energy near-UV light leads to problems with scalability, chemoselectivity, and catalyst deactivation, which have limited the synthetic applications of this combination. Herein, we report a method for red-light-driven nickel-catalyzed cross-coupling reactions of aryl halides with 11 different types of nucleophiles using a polymeric carbon nitride (CN-OA-m) as a photocatalyst. This semiheterogeneous catalyst system enabled the formation of four different types of carbon–heteroatom bonds (C–N, C–O, C–S, and C–Se) with a wide range of substrates (more than 200 examples) with yields up to 94%. Moreover, the photocatalyst is easily recovered and recycled, which makes it a promising new tool for the development of other reactions involving red-light metallaphotoredox catalysis.